Nighttime Blood Pressure and White Matter Hyperintensities in Patients With Parkinson Disease. (July 2013) - Oh, Yoon-Sang; Kim, Joong-Seok; Yang, Dong-Won; Koo, Ja-Seong; Kim, Yeong-In; Jung, Hae-Ok; Lee, Kwang-Soo
<x xml:space="preserve">Abstract</x> Increasing evidence indicates that nocturnal blood pressure level and/or loss of nocturnal blood pressure dips are sensitive markers of cardiovascular morbidity and mortality. Several studies have suggested that blunted heart rate variability and nocturnal decline in heart rate are also associated with target organ damage. These phenomena occur relatively commonly in patients with Parkinson disease (PD); however, few studies have assessed the consequences of these abnormalities in patients with PD. We investigated the influence of circadian changes in blood pressure and heart rate on white matter hyperintensities (WMHs) in patients with PD. The presence of nocturnal hypertension was associated with increased WMH score, and nighttime systolic pressure was closely related with white matter changes. Blunted heart rate variability and nocturnal decline in heart rate were also related to increasing WMH scores. The non-dipping phenomenon did not influence WMHs. These findings suggest that white matter changes are related to circadian autonomic dysfunction, particularly nocturnal hypertension in patients with PD. Therefore, it is important to monitor nocturnal blood pressure status, because modifying these circadian regulatory disturbances can be beneficial to protect against vascular brain damage in patients with PD. (Author correspondence: neuronet@catholic.ac.kr)